Disorientations: Chinese Literature in the American University - Yu, Pauline (Surfaces, 1995)
This paper examines the various scholarly and institutional mediations by which Chinese literature has been studied in the West, starting with the governing assumptions of nineteenth-century European philology and moving to the defense-strategical motivations behind the development of area studies programs after World War II, to the burgeoning of East-West comparative literature, and finally to the often concealed, but usually overtly universalizing presumptions of contemporary Western theory. While I do not wish to argue for a parochial cultural essentialism or exceptionalism that would insulate Chinese literary traditions from the analytical tools of Western academic practice, I do feel that concepts with claims to be "global" have not really been seriously tested by works embedded in very different histories and contexts, and questions about the function and nature of humanistic discourse have been assumed to be transportable rather than subject to confrontation and transformation from those works. Finally, I point out how the asymmetry in this relationship between Western theory and other traditions has been institutionalized in the typical departmental structure of the American university, a situation that is only now being subject to challenge.